Advanced Nanomaterials in Biomedical Application - Kaluđerović, Goran; Pantelić, Nebojša (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue on "Advanced Nanomaterials in Biomedical Application" aimed to showcase the most recent advances in nanomaterials, not only in terms of their synthesis and characterization, but also their technological application. This Special Issue welcomed the submission of original research articles and reviews. Research areas include all types of nanomaterials used in the development of medical applications (e.g., therapeutic: anticancer, antibacterial, toxicology; diagnostic: imaging; nanodevices, and others).